2000
DOI: 10.1097/00001888-200005000-00018
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Outcomes of the New Pathway Program at Harvard Medical School

Abstract: Differences between NP and traditional students in the humanism domain first appeared during medical school and residency and remained significant well into practice, suggesting that humanistic medicine can be taught and learned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
82
0
7

Year Published

2003
2003
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(93 citation statements)
references
References 6 publications
3
82
0
7
Order By: Relevance
“…Table 2 classifies the study outcomes according to whether the competencies of graduates of problem-based learning curricula were better than (positive), the same as (no different) or worse than (negative) those of graduates in the control group (a more detailed version of Table 2 is in Appendix 3, available online at www.cmaj.ca/cgi/content/full/178/1/34/DC2). The outcomes of 6 studies 28,[31][32][33][34][35]37 could potentially be confounded by other reported changes in problem-based-learning curricula (see remarks column of Table 2 for details). These outcomes were excluded when we assessed the levels of evidence.…”
mentioning
confidence: 99%
“…Table 2 classifies the study outcomes according to whether the competencies of graduates of problem-based learning curricula were better than (positive), the same as (no different) or worse than (negative) those of graduates in the control group (a more detailed version of Table 2 is in Appendix 3, available online at www.cmaj.ca/cgi/content/full/178/1/34/DC2). The outcomes of 6 studies 28,[31][32][33][34][35]37 could potentially be confounded by other reported changes in problem-based-learning curricula (see remarks column of Table 2 for details). These outcomes were excluded when we assessed the levels of evidence.…”
mentioning
confidence: 99%
“…Peter et al 13 Avaliações dos graduados mais positivas em 3 dos 8 aspectos do domínio da medicina humanística, bem como em 2 dos 9 aspectos do domínio da aprendizagem social.…”
unclassified
“…They interpred that Problem-based learning during medical school has positive effects on physician competency after graduation, mainly in social and cognitive dimensions (20). According to Peters et al's (21) research, PBL curriculum alumni rated their preparation to practice medicine in a humane fashion more highly than did graduates of its conventional curriculum and expressed more confidence in their ability to manage patients with psychosocial problems (21). Graduates of the PBL curriculum showed higher self-ratings on communication skills in dealing with the social context of patients (7 …”
Section: Discussionmentioning
confidence: 99%